Intermediation capabilities of Information and Communication Technologies (ICTs) in Ghana's Agricultural Extension System - Munthali, N.; Lie, R.; Lammeren, R. van; Paassen, Annemarie van; Asare, R.; Leeuwis, Cees (Wits School of Literature, Language and Media (SLLM), 2021)
Information and communication technologies (ICTs), specifically those that are digital and interactive, present opportunities for enhanced intermediation between actors in Ghana’s agricultural extension system. To understand these opportunities, this study investigates the capabilities of ICTs in support of seven forms of intermediation in the context of agricultural extension: disseminating (information), retrieving (information), harvesting (information), matching (actors to services), networking (among actors), coordinating (actors), and co-creating (among actors). The study identifies the types of ICTs currently functioning in Ghana’s agricultural system, and applies a Delphi-inspired research design to determine the consensus and dissensus of researchers, scientists, and practitioners about the potential of these ICTs to support each of the seven intermediation capabilities. The findings reveal that experts reached consensus that interactive voice response (IVR) technologies currently have the highest potential to support disseminating, retrieving, harvesting, and matching. Meanwhile, social media messaging (SMM) technologies are currently seen as highly capable of supporting coordinating and, to a lesser extent, co-creating, but no consensus is reached on the potential of any of the technologies to support networking.